Output-Based Aid in Health : The Argentine Maternal-Child Health Insurance Program - Johannes, Lars (World Bank, Washington, DC, 2012)
This newsletter describes how the Argentine Maternal-Child Health Insurance Program uses an interesting approach of combining output-based contracting with an output-based funding mechanism. Particularly innovative is the combination of enrollment numbers and performance indicators as a way to address the tradeoff between quantity and quality. The program's transfer of performance risks to health service purchasing units and service providers helps increase accountability and the program design has also allowed the government to introduce significant structural changes to the health system at provincial level such as linking financing to results (service delivery and outcomes), implement output and quality information systems with regular audits, improve costing and pricing capacity, and establish performance based incentives for health personnel. The paper gives conclusions and touches on how the achievements so far show the advantages of the concept of combining output-based contracting with output-based funding.